Does Augmented-Reality Head-Up Display Help? A Preliminary Study on Driving Performance Through a VR-Simulated Eye Movement Analysis - Ma, Xiangdong; Jia, Mengting; Hong, Zhicong; Kwok, Alex Pak Ki; Yan, Mian (IEEE access, 2021)
Augmented reality heads-up display (AR-HUD) is becoming increasingly popular as a way to keep drivers focusing on roads. By overlaying visuals on the windshield, AR-HUDs improve the drivers' view of the environment outside the car, creating a stronger sense of awareness of the surroundings. However, whether AR-HUD and to what extent different AR-HUD layouts could improve drivers' driving performance are still questionable. Unfortunately, AR-HUD is still at a research stage, not yet fully commercialized. Hence, there are few actual products in the market available for testing. For this reason, this study developed a virtual reality driving simulator to tested drivers' driving performance environment under three scenarios: without AR-HUD, dispersed layout (AR-HUD1), and dense layout (AR-HUD2). Twelve subjects were invited to join the experiment. Their driving performance was measured in various aspects. This study showed that AR-HUD with interfaces that conform to human-computer interaction principles and visual design rules could improve cognitive resource allocation and promote driving safety. Conversely, a poor designed AR-HUD could negatively impact driving safety.